The intersectionality-based policy analysis framework: demonstrating utility through application to the pre-vaccine U.S. COVID-19 policy response - Debbie L. Humphries; Michelle Sodipo; Michelle Sodipo; Skyler D. Jackson (Frontiers Media S.A., 2023)
Few guidelines exist for the development of socially responsible health policy, and frameworks that balance considerations of data, strategy, and equity are limited. The Intersectionality-Based Policy Analysis (IBPA) framework utilizes a structured questioning process to consider problems and policies, while applying guiding principles of equity, social justice, power, intersectionality, and diversity of knowledge and input. We apply the IBPA framework's guiding principles and questions to the pre-vaccine U.S. COVID-19 policy response. Results suggest the IBPA approach is a promising tool for integrating equity considerations in the development of policy solutions to urgent US public health challenges, including the COVID-19 pandemic. We found the IBPA framework particularly useful in differentiating between problems or policies and representations of problems or policies, and in considering the impacts of representations on different groups. The explicit inclusion of short-, medium- and long-term solutions is a reminder of the importance of holding a long-term vision of the equitable public health system we want while working towards immediate change.